PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS SCIENTIFIC INVESTIGATION UNTUK MELATIH KETERAMPILAN PROSES SAINS PADA MATERI FLUIDA STATIS KELAS XI SMA - Norazlina Norazlina; Mitri Irianti; Nur Islami (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The development of Science and Technology has led the word to the industrial revolution 4.0 which requires a teacher to be able to keep up with the times. In addition, the lack of use of innovative and interesting leanring tools for students, so it is necessary to develop practical and interesting teaching materials based on scientific investigation. Thare are also learning tools used in the form of lesson plans and LKPD sheets. This study aims to develop scientific investigation-based learning tools to train science process skills on static fluid material for class XI SMA. The type of research used is Research and Development (R&D) using a modified ADDIE model consisting of only 3 stages, namely the analysis, design and development stages. The types of date obtained in this study are quantitative date in the form of validity values and learning tools and qualitative date obtained form criticism and suggestions from the validator. The date collection instrument used is in the form of a learning device sheet. The tade were alalyzed descriptively to determine the validity of the learning device using the Likert Scale formula. The results of the validation assessment from the validator were alalyzed on each assessment indicator so that the level of validity of ecach learning device was obtained. Validation was carried out 2 times, the results of the validation of I learning device contained an average ratingof less than 3 and was invalid. Then the learning device is repaired according ti the suggestions for improvement. The results of the second validation of the learning device as a whone are in the good category and are declared valid. The average result of the II RPP validation as as whole is 3,59, the average result of the II LKPD validation as a whole is 3,47. So it can be concluded that from the assessment scores that have been described, scientific investigation-based learning tools to practice science process skills on static fluid material for class XI SMA are valid and svitable for use in the physics learning process.Key words: Device Learning, Scientific Investigation, Static Fluid.